Hajj during the Dutch East Indies Pandemic in the 19th–20th Centuries - Johan Wahyudi; M Dien Madjid (Institut Agama Islam Sumatera Barat, 2023)
This paper discusses about the phenomenon of Hajj during the pandemic in the XIXth to mid-XXth centuries in the Dutch East Indies with a focus on the governance of health services carried out by the Dutch East Indies government. This research uses historical research methods to explore various relevant primary and secondary sources, such as historical archives, government documents, travel records, and historical literature. The main finding of this research is that the pandemic that occurred during that time, such as the cholera outbreak, had a significant impact on the Hajj journey and the welfare of the pilgrims. The Dutch East Indies government undertook various efforts to manage health services during the Hajj journey, including the provision of medical facilities and quarantine. The results of this study provide a deeper understanding of how the Dutch East Indies government dealt with the pandemic during that time and how it affected the Hajj experience and health care governance efforts in the context of Dutch East Indies history. The findings can provide valuable insights for understanding the history and context of the pandemic in global and regional history.